Induced Osteogenesis in Plants Decellularized Scaffolds - Lee, Jennifer (Sci Rep, 2019)
A three-dimensional (3D) culture system that closely replicates the in vivo microenvironment of calcifying osteoid is essential for in vitro cultivation of bone-like material. In this regard, the 3D cellulose constructs of plants may well serve as scaffolds to promote growth and differentiation of osteoblasts in culture. Our aim in this study was to generate bone-like tissue by seeding pluripotent stem cells (hiPSCs), stimulated to differentiate as osteoblasts in culture, onto the decellularised scaffolds of various plants. We then assessed expression levels of pertinent cellular markers and degrees of calcium-specific staining to gauge technical success. Apple scaffolding bearing regular pores of 300 μm seemed to provide the best construct. The bone-like tissue thus generated was implantable in a rat calvarial defect model where if helped form calcified tissue. Depending on the regularity and sizing of scaffold pores, this approach readily facilitates production of mineralized bone.